1967
DOI: 10.1002/andp.19674740502
|View full text |Cite
|
Sign up to set email alerts
|

On the Hollow Cathode Effect Mechanism

Abstract: On basis of new results concerning the dependence of the discharge current on the intercathode spacing and the cathode fall potential, the main characteristics of the hollow cathode effect (H.C.E) in a plane-parallel geometry are defined.In order to explain the particularities of the H.C.E., a mechanism is p r o p e d that regards the discharge current amplifications and the enhancement of the negative glow plasma as a consequence of the plasma beam instabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1970
1970
1984
1984

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…In this section we show that the repeated bursts of electrical noise from our discharge tube are consistent with an interaction of secondary electrons and a decaying plasma in a similar way to that suggested by Popovici et al (1967) for self-sustaining hollow-cathode discharges. In our case successive bursts appear to correspond to resonances of progressively lower mode number, terminated either when all the plasma is swept from the hollow-cathode or when the fundamental frequency is reached.…”
Section: Generalsupporting
confidence: 79%
See 4 more Smart Citations
“…In this section we show that the repeated bursts of electrical noise from our discharge tube are consistent with an interaction of secondary electrons and a decaying plasma in a similar way to that suggested by Popovici et al (1967) for self-sustaining hollow-cathode discharges. In our case successive bursts appear to correspond to resonances of progressively lower mode number, terminated either when all the plasma is swept from the hollow-cathode or when the fundamental frequency is reached.…”
Section: Generalsupporting
confidence: 79%
“…Young (1968) detected bursts of microwave emission at the onset of these discharges. From this and other evidence he concluded that the beam plasma interaction proposed by Popovici et al (1967) was probably responsible for the ionization. The present work does not fully support this conclusion ; it is concerned with a form of beam-plasma interaction which does not appear to contribute significantly to the ionization, but is undoubtedly a hollow-cathode 1292 0.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations